Analisis Kepuasan Wisatawan di Kaamala Resort Ubud - Susila, I Made Gede Darma; Nugraha, I Wayan; Sutapa, I Ketut (Journal of Hospitality Accommodation Management (JHAM), 2024)
Tourists’ response to expected services constitutes their satisfaction. If the outcome exceeds their expectations, tourists feel satisfied; conversely, they may not. The purpose of this research is to examine how service quality and facilities influence tourist satisfaction, identify key factors affecting it, and analyze the extent of their impact. The study population consists of tourists staying at Kaamala Resort Ubud. The sample, comprising 200 respondents, was selected using non-probabilistic accidental sampling. Data were collected through observation, questionnaires, interviews, and literature review. Quantitative descriptive analysis and multiple linear regression analysis were employed for data analysis. The research results indicate that service quality and facilities partially influence tourist satisfaction. Moreover, both factors have a positive simultaneous impact on tourist satisfaction. One variable, as indicated by the coefficient of determination test, significantly influences tourist satisfaction, accounting for 59%. Hotel management is advised to enhance customer satisfaction by prioritizing service quality and the availability of facilities.